Analisis Strategi Market Share dan Peningkatan Indeks Harga Saham Perusahaan Pada Novel Resign Karya Almira Bastari - Agustin Dwi Lestari; Dinda Himatul Amalia; Eva Dwi Kurniawan (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2024)
The aim of this research is to analyze the influence of market share in the novel "Resign" by Almira Bastari on company shares. The method used in this research is a qualitative description method. This method analyzes presentation data in the novel "Resign" by Almira Bastari. The object studied in this research is the function of market share and share on changes in the company's economy in the novel 'Resignation' by Almira Bastari. The data source for this research is the novel "Resign" by Almira Bastari. Published in 2018 by the publisher Gramedia Pustacautama. Data collection techniques in this research used reading and note-taking techniques. Based on the research results, it can be concluded that the market share strategy and increasing the company's share price index influence the running of a business in the company.